1999
DOI: 10.2307/3285649
|View full text |Cite
|
Sign up to set email alerts
|

First Paleoparasitological Analysis of a Midden in the Aleutian Islands (Alaska): Results and Limits

Abstract: Excavations on Buldir Island, Aleutian Islands, Alaska, have revealed the remains of several features dated between the 13th and 17th centuries A.D. Soil from an open-air workshop, represented by 2 excavated pits, and a structure built of whale bones were sampled for evidence of parasites and microfloristic remains. Two groups of helminth eggs (Diphyllobothrium and Ankylostomidae) were identified in samples from the open-air pits; microfloristical remains were found in all samples. This is the first paleoparas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Among other well-known finds are the Pazyryk bodies in the Altai mountains (Hart Hansen 1998). Several reports of parasitic eggs exist from the finds mentioned above (Zimmerman 1998, Bouchet et al 1999, Aufderheide & Rodríguez-Martín 1998.…”
Section: Mummified Bodiesmentioning
confidence: 99%
“…Among other well-known finds are the Pazyryk bodies in the Altai mountains (Hart Hansen 1998). Several reports of parasitic eggs exist from the finds mentioned above (Zimmerman 1998, Bouchet et al 1999, Aufderheide & Rodríguez-Martín 1998.…”
Section: Mummified Bodiesmentioning
confidence: 99%
“…Lutz 1973;Shaw 1998;Frink 2007) and occasionally investigated using environmental archaeology approaches (e.g. Bouchet et al 1999;Knudson et al 2004), though never using archaeoentomological methods. One of the most promising applications of archaeoentomology at Nunalleq thus lies in its use in examining the spatial organisation of activities.…”
Section: Methodological Implicationsmentioning
confidence: 99%
“…In addition to the findings cited above, BOUCHET et al 17,20 found eggs from genus Diphyllobothrium in samples from Alaska.…”
Section: North and Central Americamentioning
confidence: 97%